Problems by Notaries Regarding The Deed of Establishment of a Limited Liability Legal Entity Related to The Online Single Submission (OSS) System Licensing in Semarang City - Maryudanto, Septian Mahar; Shallman, Shallman (TABELLIUS: Journal of Law, 2025)
Abstract. Commercial or operational business permits are issued by the OSS Institution for and on behalf of the Minister, Head of Institution, Governor, or Regent and Mayor after the business actor obtains a business permit and to carry out commercial or operational activities by fulfilling the requirements or commitments. The OSS Institution is responsible for issuing Business Identification Numbers (NIB), location permits, and business permits. Basically, this regulation aims to cut down the complicated process of issuing business permits. The purpose of this study is to find out, analyze / analyze: 1) How to make a limited liability company deed 2) the effectiveness of business permit registration through the Online Single Submission (OSS) system for registration of Limited Liability Company Legal Entities (PT) by a Notary as a means of One-Stop Integrated Licensing Services (PPTSP) in the Semarang City area. 3) obstacles and solutions faced in using the Online Single Submission (OSS) system for registration of Limited Liability Company Legal Entities (PT) in the Semarang City area. The approach method used in this research is sociological juridical, namely legal research conducted on the real conditions of society or the community environment with the aim and objective of finding facts (fact-finding) and then identifying them (problem-identification) and ultimately leading to problem solving (problem-solution). The results of the study are: 1) How to make a limited liability company deed. 2) The effectiveness of registering a business permit through the Online Single Submission (OSS) system for the registration of a Limited Liability Company (PT) Legal Entity by a Notary as a means of the One-Stop Integrated Licensing Service (PPTSP) in the Semarang City area is still ineffective because the implementation of OSS in Semarang City from the beginning of the issuance of Government Regulation No. 24 of 2018 concerning Electronically Integrated Business Licensing Services in the first year for the administration of legal entities still causes problems. 3) The obstacles faced include the system still tends to be weak. The OSS system does not carry out the licensing process as a whole. Many business actors establishing a limited liability company (PT) still need the help of consultants to fill out the forms in the OSS system. Keywords: Legal Entity; Limited Liability Company; OSS.